Estudo do Career Exploration Survey com estudantes do ensino secundário moçambicano - Taveira, Maria do Céu (2010)
This study presents and discusses the psychometric qualities of the Portuguese version of the Career Exploration Survey (CES, Stumpf, Colarelli & Hartman, 1983; Taveira 1997) in a sample of Mozambican students (n = 314) of both sexes (boys n = 120, 38.2%; girls n = 194, 61.8%), attending the 12th grade in six secondary schools (n = 3 public, private n = 3) located in the cities of Maputo and Matola, in the south of Mozambique. In terms of internal consistency, the CES items register Cronbach Alpha coefficients of 0.83. The analysis of the values of Kaiser test-Meyer-Olkin (KMO = 0.709) and of the level of significance registered in Bartlett’s test of sphericity (p = 0.00) suggested the adequacy of the data for an exploratory factorial study. As a result of this, it was chosen a solution of eight factors, consistent with the Portuguese measurement model for 12th grade students, explaining 42.50% of the total variance of the career exploration of the sample, and with internal consistency coefficients ranging from 0.57 (Factor 7, Amount and Satisfaction with Information) to 0.83 (Factor 1, Exploration and Decision Stress). This is a first exploratory study with the CES in Mozambique; it is not possible to conclude definitively on its validity. However, results indicate that this instrument provides initial evidence of validity and reliability for support its use in the Mozambican context. Este estudo apresenta e discute as qualidades psicométricas da versão portuguesa do Career Exploration Survey (CES, Stumpf, Colarelli & Hartman, 1983; Taveira, 1997) em uma amostra de estudantes moçambicanos (n = 314) de ambos os sexos (rapazes n = 120 , 38,2%; raparigas n = 194, 61,8%), a frequentar a 12 ª classe em seis escolas secundárias (n = 3 públicas, n = 3 privadas), localizadas nas cidades de Maputo e Matola, no sul de Moçambique. Em termos de consistência interna, os itens da CES registam coeficientes alfa de Cronbach de 0,83. A análise dos valores do teste de Kaiser-Meyer-Olkin (KMO = 0,709) e do nível de significância registado no teste de esfericidade de Bartlett’s (p = 0,00) sugeriu a adequação dos dados para um estudo factorial exploratório. Como resultado, foi escolhida uma solução de oito factores, consistente com o modelo de medida português para o 12º ano, explicando 42,50% da variância total da exploração vocacional da amostra, e com coeficientes de consistência interna que variam de 0,57 (Factor 7, Quantidade e Satisfação com a Informação) para 0,83 (Fator 1, Stress com a Exploração e Decisão). Este é um primeiro estudo exploratório com o CES, em Moçambique, e por isso, não é possível concluir definitivamente sobre a sua validade. No entanto, os resultados indicam que este instrumento fornece evidência inicial de validade e fiabilidade para suportar o seu uso no contexto moçambicano.